2022
DOI: 10.1186/s12909-022-03766-0
|View full text |Cite
|
Sign up to set email alerts
|

Care across the gender spectrum: A transgender health curriculum in the Obstetrics and Gynecology clerkship

Abstract: Background A lack of undergraduate medical curricula on providing healthcare to transgender and gender diverse (TGD) patients has contributed to significant health disparities for TGD communities. To address this gap, we designed and evaluated a novel curriculum to train Obstetrics and Gynecology (OB/GYN) clerkship students in caring for TGD patients. Methods Following Kern’s 6-step method for curriculum development, we created a two-part curriculu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There was 1 required intervention on this topic area that involved both the pre-clinical and clinical curriculum, as well as 5 optional interventions that were not specified as occurring in a specific part of the curriculum. Among these interventions that focused on aspects related to gender identity and affirming care: 13 significantly increased knowledge [ 25 , 61 , 62 , 68 , 71 , 73 , 75–78 , 81 , 85 , 89 ]; 7 significantly increased comfort with aspects of providing care [ 25 , 37 , 47 , 48 , 71 , 73 , 85 ]; and 4 significantly increased confidence in providing care [ 21 , 59 , 62 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was 1 required intervention on this topic area that involved both the pre-clinical and clinical curriculum, as well as 5 optional interventions that were not specified as occurring in a specific part of the curriculum. Among these interventions that focused on aspects related to gender identity and affirming care: 13 significantly increased knowledge [ 25 , 61 , 62 , 68 , 71 , 73 , 75–78 , 81 , 85 , 89 ]; 7 significantly increased comfort with aspects of providing care [ 25 , 37 , 47 , 48 , 71 , 73 , 85 ]; and 4 significantly increased confidence in providing care [ 21 , 59 , 62 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…This review sheds light on educational interventions that could be utilized to address these gaps, as there were 34 studies on interventions related to the health of people who identify as transgender or gender diverse and gender-affirming care, and 19 of these studies that showed statistically significant improvement in student outcomes. These interventions had a significant impact on multiple aspects of trainees preparation: 13 significantly increased knowledge [ 25 , 61 , 62 , 68 , 71 , 73 , 75–78 , 81 , 85 , 89 ]; 7 significantly increased comfort with aspects of providing care [ 25 , 37 , 47 , 48 , 71 , 73 , 85 ]; and 4 significantly increased confidence in providing care [ 21 , 59 , 62 , 86 ]. Educational interventions on this topic area also align with the guidance in the 2014 AAMC report.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a study conducted by Schmidt et al regarding curriculum development, only 22% felt competent to provide transrelevant services and 90% desired additional clinical training. 2 Hence, they suggested a curriculum which should include the different vocabulary used to address people with non-binary non-conforming gender expansive population and describe all the eligibility criteria for various hormonal and surgical treatments available for them. In a trial attempt to integrate TGP care into medical curriculum, significant (95%) improvement in the knowledge of students was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In a trial attempt to integrate TGP care into medical curriculum, significant (95%) improvement in the knowledge of students was observed. 2 In the study conducted by Tappy et al after a 2.5 hour training program residents felt more prepared to collect TG focused history, provide referral and access additional educational resources. 15 Steps that can be taken to address the structural, interpersonal, and anticipation barriers to transgender healthcare include enacting policy changes related to insurance coverage for gender-affirming healthcare, reforming medical school curricula to prepare future physicians to provide competent care to transgender patients and continuing education for healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation